Pengembangan LKPD Berbasis Kearifan Lokal (Lemea) untuk Melatih Keterampilan Kolaborasi Siswa SMP - Mentari Ezatalopa; Nopriyeni; Rizki Pratama (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to develop a Student Worksheet (LKPD) based on local wisdom of lemea to train the collaboration skills of junior high school students in learning conventional biotechnology. This study used a Research and Development (R&D) method with the 4D model (Define, Design, Develop, Disseminate) conducted at SMP Negeri 18 Bengkulu Tengah involving 10 students in a limited trial and 26 students in an extensive trial; LKPD validity was assessed by 3 material experts and 2 media experts, while practicality was measured through teacher response questionnaires, student response questionnaires, and observer sheets analyzed using descriptive percentage analysis. The results showed that the LKPD achieved a validity average of 97.45% (very valid category) and a practicality average of 95.1% (very practical category); the integration of local wisdom of lemea fermentation as conventional biotechnology material was assessed as highly feasible in supporting contextual, meaningful, and collaborative learning based on expert validation and observer assessments; and the developed LKPD systematically facilitated collaboration skills through Project-Based Learning syntax including active participation, effective communication, task sharing, group responsibility, and mutual respect. This study concludes that the lemea local wisdom-based LKPD has met the criteria of very valid and very practical, and therefore suitable for use as teaching material to train junior high school students' collaboration skills in conventional biotechnology learning. Keywords: Biotechnology, Collaboration Skills, Local Wisdom, LKPD, R&D